Effectiveness of Educational Intervention on Improving Preventive Behaviors in Fireworks Injuries: Applying the Extended Parallel Process Model - Majid Barati; Khadijeh Ezzati Rastgar; Sharareh Bagheri; Jahanbakhsh Usefi; Ameneh Hosseini; Samrand Saeedi; Golaleh Parandan (Hamadan University of Medical Sciences, 2021)
Aims: Charshanbeh Suri is one of the most important Iranian ceremonies every year when many people are injured due to the use of explosives on the day. The present study aimed to investigate the effectiveness of the developed parallel process model in injury prevention in students. Materials & Methods: This experimental study was conducted in 2020-21 with 240 male students in Sanandaj who were randomly and equally divided into experimental and control groups. The intervention consisted of two 90-minute training sessions in the form of lectures, questions, and answers, group discussions, and screenings of related videos. The researcher-made questionnaire based on the model constructs of the developed parallel process, the validity, and reliability of which were confirmed, was used before the intervention and two months after the intervention. Data were analyzed by independent t-test and logistic regression analysis using SPSS 16 software. Findings: The mean age of students was 15.82±1.05 years. There was no significant difference in fireworks behavior between the two groups before the intervention, and 88% of the students used explosives during the Charshanbeh Suri ceremony. The results of the logistic regression test before the intervention showed that the perceived threat predicted the non-use of incendiary materials. The effectiveness of the educational intervention caused the students in the experimental group to be in the path of risk control, and the use of incendiary substances after the intervention in the experimental group was significantly reduced (p<0.001). Conclusion: Education with the content of sensitization and fear and efficiency is an appropriate educational intervention in reducing Charshanbeh Suri events in adolescents.